Managing learning in virtual settings the role of context - Figueiredo, Antonio Dias 1946-.; Afonso, Ana Paula 1973-.; Gale Group (Hershey, Penn. Information Science Pub., 2006)
"This book emphasizes the role of context in the development and management of virtual learning environments"--Provided by publisher.
Chapter 1. Context and learning: a philosophical framework -- Chapter 2. Virtual settings - e-learning as creating context -- Chapter 3. Context engineering for learning : a socio-technical approach -- Chapter 4. The role of context when implementing learning environments : some key issues -- Chapter 5. Space as a learning context : quality, form and pedagogy -- Chapter 6. The dynamics of online collaboration : team task, team development, peer relationship, and communication media -- Chapter 7. Designing for unique online learning contexts - the alignment of purpose, audience and form of interactivity -- Chapter 8. Communities as context providers for Web based learning -- Chapter 9. Activity theory and context : an understanding of the development of constructivist instructional design model -- Chapter 10. The distance from isolation : why communities are the logical conclusion in e-learning -- Chapter 11. Designing for context in virtual settings -- Chapter 12. The voice of the online learner -- Chapter 13. Learning agency in new learning environments : an Australian case study of the influence of context -- Chapter 14. New wine or new bottles - what's new about online teaching? -- Chapter 15. Quality assurance during distributed collaboration : a case study in creating a cross-institutional learning community -- Chapter 16. A constructivist view of knowledge management in open source virtual communities -- Chapter 17. Building a learning community on-line.
Electronic reproduction.
Keywords: Distance education -- Computer-assisted instruction -- Management; Web-based instruction -- Management; Electronic books